Comparison of different activators of coagulation by turbidity analysis of hereditary dysfibrinogenemia and controls. Issue 2 (12th March 2021) - Marchi, Rita; Neerman-Arbez, Marguerite; Gay, Valérie; Mourey, Guillaume; Fiore, Mathieu; Mouton, Christine; Gautier, Philippe; De Moerloose, Philippe; Casini, Alessandro
Abstract : Turbidity analysis is widely used as a quantitative technique in hereditary dysfibrinogenemia. We aimed to compare several coagulation triggers in hereditary dysfibrinogenemia and control plasmas. We included 20 patients with hereditary dysfibrinogenemia, 19 with hotspot mutations Aα Arg35His ( n  = 9), Aα Arg35Cys ( n  = 2), γ Arg301His ( n  = 6), γ Arg301Cys ( n  = 2), and one with Aα Phe27Tyr, and a commercial pooled normal plasma. Fibrin polymerization was activated by bovine or human thrombin or tissue factor (TF), in the presence or absence of tissue type plasminogen activator. The lag time (min), slope (mOD/s), maximum absorbance (MaxAbs, mOD), and area under the curve (AUCp, OD s) were calculated from the fibrin polymerization curves and the time for 50% clot degradation (T50, min), AUCf (OD s) and the overall fibrinolytic potential from fibrinolysis curves. The lag time was significantly shorter and AUC increased in Aα Arg35His patients with bovine thrombin as compared with human thrombin. The MaxAbs and AUCp were significantly higher in γArg301His patients with bovine thrombin compared with human thrombin. Fibrin polymerization parameters of patients' samples were closer to those of control when assessed with TF compared with both human and bovine thrombin. T50 and overall fibrinolytic potential were similar in all samples regardless of the coagulation trigger used, however, with TF the AUCf of Aα Arg35His and γ Arg301His groups were significantly decreased compared with control. Bovine and human thrombin cannot be used equally for studying fibrin polymerization in hotspot hereditary dysfibrinogenemia or control plasmas.